Winged Words from the Bible in the Modern Belarusian (lexicographic aspect) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The research material is biblical expressions, which function as winged in the Modern Belarusian. The subject of research is the lexicographical description biblical winged words (expressions). The purpose of research to determine the principles and create a pattern of systemic and comprehensive linguistic description of winged words, which are derived from the Bible and are used in the Modern Belarusian. This description will be in a special, normative (explanatory) dictionary with historical and etymological commentary and equivalents in Modern Russian. The research methodology is (1) a linguistic method of structural-semantic modeling of winged units (expressions) in synchronous and diachronic aspects in a wide factual material, as a result of a complex descriptive and comparative analysis of facts of different languages, and (2) methods of fixation, systematization and lexicographical description of winged units according to the principle of completeness of the phraseological dictionary. The study found that in the Modern Belarusian is actively used at least 600 winged words (expressions), which are derived from the Bible. Such expressions must systematically and comprehensively described separately in a special linguistic dictionary “Winged words in the Modern Belarusian: from Bible”. A dictionary should be qualified as a linguistic normative type (explanatory) of a dictionary with historical, etymological and comparative components. Biblical winged words (expressions) should be codified in the dictionary according to various parameters of the literary norm (standard form, meaning, stylistic characteristic, use in speech, biblical origin, the ratio of content and form to the biblical original). Each winged word (expression) should be described separately in the dictionary: (1) the basic form and all variant and optional forms, (2) stylistic, functional and (if necessary) expressive and evaluative features, (3) historical and etymological commentary, (4) biblical context, (5) linguistic and cultural commentary, (6) explanation of the meaning and (if necessary) situations of use, (7) examples of use in speech (mass media, journalism, literary works), (8) equivalents in Modern Russian. The principles and parameters of the lexicographic description of biblical expressions that are used as winged in the Modern Belarusian will be used to create the dictionary “Winged words in the Modern Belarusian: from Bible”.
Keywords: Bible; Modern Belarusian; expression; a winged word; dictionary; literary norm; etymology; comparison; equivalent; Modern Russian